KARAKTERISTIK KLINIKOPATOLOGI PENYAKIT HIRSCHSPRUNG DI RSUP SANGLAH DENPASAR TAHUN 2019-2020 - Wilananda, Ida Bagus Ardya Kurnia; Dewi, I Gusti Ayu Sri Mahendra; Winari, Ni Wayan; Sriwidyani, Ni Putu (E-Jurnal Medika Udayana, 2022)
ABSTRACT Hirschsprung's disease is an abnormal condition of the colon with characteristics of the Meissneri submucosus, myenteric plexus and Aurbachi plexus without parasympathetic ganglion cells. Manifestations of Hirschsprung's disease are seen in the discharge of meconium that does not come out within 24 hours. Then there are signs of obstruction to the gastrointestinal tract, vomiting bile, constipation, and irregular bowel movements. In 2017, 2.5 million children died in the first month of life worldwide. 47% of deaths of children under the age of 5 years occur in newborns, which is about 7,000 deaths. Cases of Hirschsprung's disease itself occur in 1:5000-7000 births, with cases in boys 4 times more than girls. This study aims to determine the clinicopathological characteristics of Hirschsprung's disease at Sanglah Hospital Denpasar in 2019-2020 based on clinical symptoms, age, gender, and location of the aganglionic bowel segment. This study was carried out in 2021 at the Sanglah Hospital Denpasar Anatomical Pathology (PA) installation, using data from the years 2019-2020. It was conducted using a cross-sectional method, with secondary data in the form of patient data available at the Sanglah Hospital Denpasar PA Laboratory, and total sampling. SPSS version 26 was used to analyze the data. The results of this study showed that there were 78 patients with Hirschsprung's disease at Sanglah Hospital Denpasar in 2019-2020 and all of them met the criteria of inclusion. Most cases of Hirschsprung's disease in Sanglah Hospital Denpasar experienced the most flatulence, namely 38 cases with a percentage of 36.5%. Cases were dominated by patients within age of 0-12 months with total of 64 people with 82.1% percentage, and dominated by men as many as 50 people with 64.1% percentage. The aganglionic most frequently found in the rectum as many as 49 people with a percentage of 62.8%. It was concluded from the study result that Hirschsprung's disease patients at Sanglah Hospital in 2019-2020 were mostly male, mostly in the age range 0-12 months, with the most clinical symptoms being flatulence, and the most common aganglionic location found in the rectum. This result may then be used as a basis and also study material for further related research and learning Keywords : Hirschsprung's disease, congenital megacolon, aganglionic, clinicopathological characteristics